2020
DOI: 10.1021/acsanm.0c00075
|View full text |Cite
|
Sign up to set email alerts
|

Outer Tube-Selectively Boron-Doped Double-Walled Carbon Nanotubes for Thermoelectric Applications

Abstract: We demonstrate the synthesis of double-walled carbon nanotubes (DWNTs) with a selectively boron-doped outer tube via the thermal diffusion method. Such selective boron-doping in the outer tubes alters the electronic properties of the outer tubes while keeping the intrinsic properties of the inner tubes intact, thereby resulting in highly enhanced thermoelectric performance of the DWNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The results of the model experiment suggesting semiconducting properties of CNTs containing boron impurity atoms are in agreement with practice [119]. It was found that the presence of boron impurity atoms leads to the above-described changes in the band gap and the conclusion was made that one should expect the resistivity of nanotubes to decrease with an increase in temperature.…”
Section: Simulation Of Carbon Nanotubes With Different Contents Of Bo...supporting
confidence: 81%
See 1 more Smart Citation
“…The results of the model experiment suggesting semiconducting properties of CNTs containing boron impurity atoms are in agreement with practice [119]. It was found that the presence of boron impurity atoms leads to the above-described changes in the band gap and the conclusion was made that one should expect the resistivity of nanotubes to decrease with an increase in temperature.…”
Section: Simulation Of Carbon Nanotubes With Different Contents Of Bo...supporting
confidence: 81%
“…This effect originates from the high dispersion of copper and hence improved copper particle interaction with the CNT carrier having a suitable surface acidity. H. Muramatsu et al reported recently [28] a nanoelectronic application of multi-walled nanotubes containing boron impurity atoms due to their thermoelectric properties. The study included selective saturation of outer tubes which proved to increase the electrical and thermal conductivity of multi-walled boron-carbon nanotubes.…”
Section: Scientific Prerequisites For Boron Modification Of Pure Carb...mentioning
confidence: 99%
“…[54] The effect on the thermoelectric performance of boron-doped CNTs may be the increase of oxygen functional groups, which form structural defect sites (such as edges, voids, and point defects) on the surface of carbon nanotubes during the binding process of CNTs. [46] The B1s spectra of pristine CNTs and boron-doped CNTs with different doping contents were measured by XPS (Figure 4) to estimate the boron concentration, and Table 1 summarizes the different atomic contents. With the increase of H 3 BO 3 content, boron-doped CNTs were observed to have undesired products boron clusters and B 4 C, as evidenced by the results of XPS spectroscopy and Raman spectroscopy, where boron atoms were introduced into carbon nanotubes by sintering substitution.…”
Section: Resultsmentioning
confidence: 99%
“…[43,44] Unlike chemical doping, in this method, the boron atoms are stable after entering the carbon nanotube lattice, and the dopants interact covalently with the host atoms, exhibiting a strong capacity to modify the electronic properties of carbon nanotubes, and the resulting doped carbon tubes will have a high degree of structural stability. [45,46] At this stage, boron-doped carbon tubes are mainly doped in situ by laser ablation, [47] arc discharge, [48] and chemical vapor deposition (CVD) [49,50] or by synthesis through postreaction. [51] For the substitution reaction of CNTs B x C 1Àx , the following chemical reactions have been previously proposed…”
Section: Introductionmentioning
confidence: 99%
“…Purification of the as‐synthesized CNTY with 1.0 M HCl increases the thermopower to 46 µV K −1 (Table S3, Supporting Information), but the purified CNTY still contains 14 wt.% Fe, suggesting that the perfectly purified CNTY with no residual Fe might have an increased thermopower, as shown in previous literatures reporting the high thermopowers (60–100 µV K –1 ) of DWCNTs. [ 32,33 ] When the purified CNTY was p ‐doped, the suppression effect of the residual Fe catalyst could be overcome and thus the thermopower increased to 60 µV K −1 . Therefore, effective p ‐doping can optimize the charge carrier injection into CNTY and consequently increase the electrical conductivity alongside the thermopower.…”
Section: Resultsmentioning
confidence: 99%